1985
DOI: 10.1111/j.1365-2672.1985.tb01470.x
|View full text |Cite
|
Sign up to set email alerts
|

A note on the isolation of salmonellas from environmental samples using three formulations of Rappaport's broth

Abstract: The efficiency of isolation of salmonellas from 412 seagull intestines and 247 polluted water samples was compared using three formulations of Rappaport's medium (RV, RV‐soya and R25). A modification of RV medium (RV‐soya) was shown to be the most efficient of the three media and it was shown that the duration of incubation of this medium could be restricted to 24 h. Inoculation ratios were compared for RV and RV‐soya and 1:100 was shown to be significantly better than 1:20. It is concluded that RV‐soya is at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The modifications of Vassiliadis (1983) to the Rappaport broth consisted of a pre‐enrichment step followed by an enrichment step, and then streaking onto solid medium. The sensitivity and specificity of RV broth was increased significantly but the method is laborious, time‐consuming and costly ( Fricker and Girdwood 1985). The same medium was modified by the substitution of the enrichment and streaking step with a semi‐solid agar ( De Smedt et al .…”
Section: Introductionmentioning
confidence: 99%
“…The modifications of Vassiliadis (1983) to the Rappaport broth consisted of a pre‐enrichment step followed by an enrichment step, and then streaking onto solid medium. The sensitivity and specificity of RV broth was increased significantly but the method is laborious, time‐consuming and costly ( Fricker and Girdwood 1985). The same medium was modified by the substitution of the enrichment and streaking step with a semi‐solid agar ( De Smedt et al .…”
Section: Introductionmentioning
confidence: 99%
“…Rappaport et al (1956) designed a medium that contained magnesium chloride (4% w/v) and a new inhibitor, malachite green (0.012% w/v). The Rappaport culture medium has been modified and evaluated by Vassiliadis and co-workers (1974Vassiliadis and co-workers ( , 1979Vassiliadis and co-workers ( , 1981aVassiliadis and co-workers ( ,b, 1983Vassiliadis and co-workers ( , 1985, Papadakis et al (1976), Harvey andPrice (1979, 1983), Kalapothaki et al (1980,1983,1986), Renaud (1983), Fricker (1984), Fricker and Girwood (1985), Watson (1985), De Smedt et al (1986), De Smedt andBolderdijk (1987), Rhodes andQuesnel (1986), Beckers et al (1987), Van Schothorst et al (1987).…”
Section: Introductionmentioning
confidence: 99%
“…This medium has subsequently become known as Rappaport-Vassiliadis (RV) medium (Papadakis & Efstratiou, 1980). Since 1976 the results of many studies of the relative efficiency of RV medium have been published, and whilst some workers maintain that the R25 medium is superior (Harvey & Price, 1983), the majority of studies have shown RV medium to be at least as efficient as R25 (Fricker, Girdwood & Munro, 1983;Fricker, 1984a;Vassiliadis et al 1979) and in some cases to be significantly better (Vassiliadis et al 1984;Fricker & Girdwood, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In comparisons of the efficiency of RV medium containing soya peptone (RV-soya) with that of the standard RV medium, we have demonstrated that RV-soya is a marginally better medium (Fricker & Girdwood, 1985;McGibbon, Quail & Fricker, 1984).…”
Section: Introductionmentioning
confidence: 99%